Immunogenicity and safety of early vaccination with two doses of a combined measles-mumps-rubella-varicella vaccine in healthy Indian children from 9 months of age: a phase III, randomised, non-inferiority trial. Issue 9 (11th September 2015) - Lalwani, Sanjay; Chatterjee, Sukanta; Balasubramanian, Sundaram; Bavdekar, Ashish; Mehta, Shailesh; Datta, Sanjoy; Povey, Michael; Henry, Ouzama
Abstract : Objective: This study (NCT00969436 ) compared the immunogenicity and safety of measles-mumps-rubella (MMR) followed by MMR+varicella (V) vaccines to (1) 2 doses of combined MMRV and (2) MMR followed by MMRV, in Indian children. Design: Phase III, open, randomised, non-inferiority study. Setting: 6 tertiary care hospitals located in India. Participants: Healthy participants aged 9–10 months not previously vaccinated against/exposed to measles, mumps, rubella and varicella or without a history of these diseases. Interventions: Participants were randomised (2:2:1) to receive 2 doses of either MMRV (MMRV/MMRV group) or MMR followed by MMRV (MMR/MMRV group) or MMR followed by MMR+V (MMR/MMR+V, control group) at 9 and 15 months of age. Antibody titres against measles, mumps and rubella were measured using ELISA and against varicella using an immunofluorescence assay. Main outcome measures: To demonstrate non-inferiority of the 2 vaccination regimens versus the control in terms of seroconversion rates, defined as a group difference with a lower bound of the 95% CI >−10% for each antigen, 43 days postdose 2. Parents/guardians recorded solicited local and general symptoms for a 4-day and 43-day period after each vaccine dose, respectively. Results: Seroconversion rates postdose 1 ranged from 87.5% to 93.2% for measles, 83.3% to 86.1% for mumps and 98.7% to 100% for rubella across the 3 vaccine groups. The seroconversion rates postdose 2 were 100% for measles, mumps and rubella and at least 95.8% for varicella across the 3 vaccine groups. Non-inferiority of MMRV/MMRV and MMR/MMRV to MMR/MMR+V was achieved for all antigens, 43 days postdose 2. The 3 vaccination regimens were generally well tolerated in terms of solicited local and general symptoms. Conclusions: The immune responses elicited by the MMRV/MMRV and MMR/MMRV vaccination regimens were non-inferior to those elicited by the MMR/MMR+V regimen for all antigens. The 3 vaccination schedules also exhibited an acceptable safety profile in Indian children. Trial registration number: NCT00969436.